Movement activity and space use : how does the moose react when the tourists come? - Höög, Nora (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2020)
Fear of predation is a major selective pressure for prey species and, although important for survival, can have adverse effects on the well-being of the animals. Human disturbance has been shown to elicit the same behavioural and physiological responses, in particular in hunted species. Using GPS-data from a heavily hunted moose population in northern Sweden, I investigated differences in habitat selection and activity patterns between two valleys contrasting in human disturbance, during both peak and low tourism seasons. The effects of temperature, precipitation, and wind speed were also considered. I found moose to alter their habitat utilisation to use more protective habitats during the peak tourism seasons in the valley with high human disturbance, whereas open habitats were used more in the valley with low disturbance. I found no evidence for activity patterns being impacted by tourism, and the weather variables were of low importance. My study suggests that moose habitat selection is indeed affected by increased human disturbance. There is a need for studies on the long-term impacts on fitness on this displacement of moose into protective habitats. In addition, bodily measurements are required to assess physiological stress responses that are not visible in the behaviour of the animals. These findings, in combination with future studies, can help managers with the planning of further recreational sprawl into moose habitats.